ChemInform Abstract: Photoassisted Synthesis of Manganese Oxide Nanostructures Using Visible Light at Room Temperature. Issue 42 (1st October 2013) - Balan, Lavinia; Ghimbeu, Camelia Matei; Vidal, Loic; Vix‐Guterl, Cathie
Abstract By tuning the precipitation conditions, a variety of nanosized morphologies (spherical, nanorods, nanoflowers, nanocubes) of manganese oxides (λ‐MnO2, γ‐Mn3O4 and MnO(OH)) is obtained from aqueous solutions of a Mn(II) salt in presence of MOH (M: Na, K, or Li) under visible light irradiation (445 nm) at room temperature.